Concise compilation of the most clinically relevant current knowledge on Brugada Syndrome - Kłakowicz, Philip; Kuc, Monika; Kułakowska, Aleksandra; Lepczyński, Bartłomiej; Lechowski, Sebastian (Journal of Education, Health and Sport, 2023)
Brugada syndrome (BrS) is a rare disease in which arrhythmogenic changes occur in patients without any structural heart pathology. Its most dangerous complication is sudden cardiac arrest, which most often occurs around the 3rd and 4th decade of life of patients. In a similar period of time (20 - 40 years of age), the first clinical manifestations of the disease also most often occur, although this can happen even sooner in the case of a malignant form of the disease. Brugada syndrome is significantly (about 8 times) more frequently diagnosed in men, and the main factors that strongly worsen its prognosis are incidents of syncope noted in the patient’s history and observed spontaneous changes in ECG studies [1][2].